PENGARUH PENDAPATAN ORANG TUA TERHADAP PERILAKU KEUANGAN MAHASISWA PENDIDIKAN EKONOMI FE UNP - Hermai Nisa Putri; Elvi Rahmi (Universitas Negeri Padang, 2019)
This study aims to analyze and see the effect of parents' income on the financial behavior of students of the Faculty of Economics, Padang State University. This type of research is associative descriptive with a population of 521 students of Economic Education at the UNP. The sampling technique is Proportional Random Sampling with a sample of 84 students. Data collection techniques used in this study were questionnaires. To ensure the questionnaire used in this study, a validity test and a reliability test were performed. The data analysis technique used is simple regression analysis with the help of SPSS version 20. Previously the prerequisite test analysis was done using the normality test, linearity test, and homogeneity test. Financial behavior of students of Economic Education, FE UNP is in quite good category. The results showed that parental income did not have a significant effect on the financial behavior of FE UNP Economic Education students. Suggestions for students whose parents are classified as low income should be wise in managing finances, especially in the aspects of making expenditure and expenditure budgets, providing funds for unexpected expenses, and saving periodically. As for students whose parents are classified as moderate and high income, they must routinely make budgets for expenditure and expenditures, and record expenses and expenditures both daily, weekly and monthly. And for students whose parents are classified as very high income must also be routine in making spending and expenditure budgets, as well as saving periodically.Keywords : parent income, and financial behavior.